(untitled) (Journal of Partial Differential Equations, 2024)
This paper is concerned with the pullback dynamics and robustness for the 2D incompressible Navier-Stokes equations with delay on the convective term in bounded domain. Under appropriate assumption on the delay term, we establish the existence of pullback attractors for the fluid flow model, which is dependent on the past state. Inspired by the idea in Zelati and Gal’s paper (JMFM, 2015), the robustness of pullback attractors has been proved via upper semi-continuity in last section.